Finance and Development, March 1982. - International Monetary Fund. External Relations Dept. (Washington, D.C. : International Monetary Fund, 1982)
This paper highlights that important changes have been made in the World Bank's management systems since Mr. A. W. Clausen became President in July 1981. The changes reflect Mr. Clausen's belief that there needs to be a more collegial approach to decision making and greater delegation of authority. The aim is that the World Bank should become more efficient and its activities should be more responsive to its clients' needs. A Managing Committee was also established to take decisions on all key issues facing the World Bank.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet